Developing a simple universal hypo-osmotic swelling test (HOST) for assessing sperm membrane integrity in pigs, rabbits, and goats. (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: The objective of this study was to evaluate the integrity of the plasma membrane for human and other domestic animal spermatozoa by the hypo-osmotic swelling test (HOST). Materials and Methods: This study was conducted on spermatozoa of three species, including pigs, rabbits, and goats. Three experiments were conducted on three animal species (pigs, rabbits, and goats) to investigate the factors affecting sperm membranes: osmotic concentration (0, 50, 100, and 150 mOsmol) and treatment time (0, 15, 30, 45, 60, and 90 min) at 37°C. Results: The results showed that treatment time and osmotic concentration influenced the integrity of the sperm membrane in the hypo-osmotic solution. In general, the experiments showed a high rate of sperm reacting to HOST at 50 and 100 mOsmol for 30–45 min. According to this study, the hypo-osmotic solution resulted in a high rate of sperm with swollen tails and a high rate of viable sperm, indicating a correlation between these factors. Therefore, it is necessary to combine both conditions to assess sperm quality. Specifically, the positive rates for the HOST reaction in pig, rabbit, and goat sperm are 46.74%, 58.28%, and 61.95%, respectively. Conclusion: To sum up, the hypo-osmotic solution with a concentration of 100 mOsmol and an incubation time of 45 min is considered the optimal and most feasible condition that can be used for all three species: pigs, rabbits, and goats.J. Adv. Vet. Anim. Res., 12(2): 477–486, June 2025http://doi.org/10.5455/javar.2025.l913